Hubungan Tingkat Pengetahuan Kesehatan Reproduksi terhadap Perilaku Seksual Remaja pada Siswa SMA di Kecamatan Baturraden dan Purwokerto - Wijayanti, Rahayu; Swasti, Keksi Girindra; Rahayu, Eva (Jurusan Keperawatan FIKES UNSOED, 2007)
The adolescentÃ¢â‚¬â„¢s reproduction health is a trend issue in their community and it becomes one of primary project of Ã¢â‚¬Å“BKKBNÃ¢â‚¬Â. If Adolescence doesnÃ¢â‚¬â„¢t get right and proper information, they will fall on into negative side from it, such as: free sex, unwanted pregnancy, abortion, and suffer from HIV/AIDS. The purpose of this study was to know the relation between knowledge of adolescentÃ¢â‚¬â„¢s reproduction health toward adolescentÃ¢â‚¬â„¢s sexual behavior in student of senior high school around sub district Purwokerto and Baturaden. The populationÃ¢â‚¬â„¢s research was students of six senior high school in sub district Purwokerto and Baturaden. The sampleÃ¢â‚¬â„¢s research was taken from 367 students according inclusive criteria. Data analysis method uses the distribution frequency and Perason CorrelationÃ¢â‚¬â„¢s Statistic test. Result of research: Respondents who have good knowledge category about adolescentÃ¢â‚¬â„¢s reproduction health is 86, 7%, Respondents who have enough knowledge category is 12%, and Respondents who have least knowledge category 0, 8%. While, the result of grade sexual behavior: Respondents who have good sexual behavior category is 72, 8%, Respondents who have enough sexual behavior category is 24, 2% and Respondents who have least sexual behavior category is 2, 7%. The obtained result of statistic test using Pearson Correlation is r=0,179, p=0,001. ItÃ¢â‚¬â„¢s indicated that there is a meaningful relation between knowledge of adolescentÃ¢â‚¬â„¢s reproduction health and adolescentÃ¢â‚¬â„¢s sexual behavior